(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
An attempt was made to apply Cumulative death Function of (Normal Log Distribution) on surviving Syrian population data during the observational years 2017.2018,2019,considering 2018 as the base year, for the period (1998-2019), the survival probabilities were calculated by using (Knapp Zeuner) method after using(Sprague coefficient table)to breakup five categories into one-age categories, the survival probabilities complement was taken to arrive at the actual death probabilities, we estimated the two parameters of distribution by using (Non-Linear Least Square Method),and calculated Unconditional and Hazard, probabilities, with the help of (SPSS28) and (R 4.2.2) program, The possibility of using death functions was tested by(Colmogorv-smirnov)&(Anderson- Darling) Test, The results came with appropriateness of distribution to the study data and possibility of using death functions of the distribution in estimating death probabilities for studied period, Hazard probability was used in building life table in Syria for the studied period, due to the least value of its mean square errors comparing with other functions.